Advancing Patient Care through the Role of Medical Professionals in Optimizing Clinical Environments: A Systematic Review - alshihri , Mohammad Hadi dafer; Alenizi, Amira Hayaf Suleima; Alanazi , Khulud Olaywi Basher; Al Juaid , Hatem Awadh Awaif; Abuhaimed, Sara Nasser Abdullatif; Alrashidi, May Awad Saeed; alshahrani, Seham sanad Shaya; Aldarami , Alhanouf Ali; Samman, Amani Salman Abbass; Alyami, Mohammed Saleh Mohammed (Journal of Ecohumanism, 2024)
The clinical environment plays a critical role in determining the quality of healthcare delivery and patient outcomes. Medical professionals, as front-line contributors, significantly influence the optimization of these environments through their expertise, interventions, and collaboration. This systematic review examines the role of medical professionals in enhancing clinical environments to improve patient care. Following PRISMA guidelines, studies from 2016 onward were analyzed to explore their contributions to workflow efficiency, resource management, and patient safety. Findings reveal that medical professionals are pivotal in driving improvements, leading to enhanced patient satisfaction, reduced medical errors, and streamlined clinical processes. The review underscores the need for targeted strategies and policy enhancements to support their role in achieving optimal clinical environments.